'Soft' actuation for dextrous hands – a 23 DOF anthropomorphic hand powered by pneumatic muscle actuators. (1st December 2008) - Caldwell, Darwin G.; Chua, Ping Yong; Amran, Mohd Zaid
The human hand with its complex anatomical and sensory structures forms an exceptional end-effector that is capable of performing countless grasping, exploratory, manipulative and prehensile tasks. Key to the effective operation of this 'hand', in terms of strength, compliance, compactness, speed of finger motions and the safe, secure handling needed to minimise potential damage to the grasped object and the hand itself, is the actuation. This paper describes the design, construction and testing of a 23 DOF robotic dextrous end-effector powered by powerful, yet compliant and accurate braided pneumatic Muscle Actuator (pMA)s. The paper discusses the control and drive systems and shows the hand performing a number of complex manipulative tasks involving dexterity and power and concludes by demonstrating that the hand can perform high speed tele-operated catching operations.